Fertirrigação por gotejamento com sistema de bombeamento fotovoltaica - Bazei, Bruna Caroline (2023)
Fertigation represents an advanced and effective approach to modern agriculture, since it has integrant such as energy, irrigation, and precise nutrient application. This technique has contributed to increase agricultural productivity, water conservation, energy resources, as well as some decrease regarding environmental impacts. So, it has played a substantial role in sustainable food production. Energy is crucial for fertigation as it is required to improve systems of pumping, filtering, water and nutrient distribution. Thus, photovoltaic solar energy has emerged as a clean and sustainable source to improve these systems, since it decreases operational costs and environmental impacts associated to agricultural production. Therefore, this study aimed at calculating the coefficients of water distribution uniformity and urea concentrations at different levels and to evaluate whether energy supply variability has intervened in uniformity coefficients. In the irrigation system, data collection was carried out using the methodology proposed by Keller and Karmeli (1975) by the flow rate determining at four emitters per lateral line. The study identified both urea concentration limit to ensure high uniformity and application efficiency, and control charts were analyzed for flow rate uniformity, pH, and electrical conductivity in a drip fertigation system with urea. Results showed that photovoltaic energy increased its output during summertime, but the system's power values remained unstable, which interfered on the irrigation process. The charge controller system did not achieve the desired stabilization in the overall system. Uniformity was rated as excellent in treatments 1 and 3 for CUC and 3 and 7 for CUD, while the lowest uniformity values were recorded for treatments 4 and 8, where the highest fertilizer concentration was applied. The distribution uniformity coefficient kept values above 90% over time in treatments 3 and 7, which had fertilizer concentration of 5 g L-1, and were classified as excellent. The study concluded that the use of charge controllers and battery banks in photovoltaic drip irrigation systems is not recommended, as the system's inclusion did not achieve the desired current and voltage stabilization. Furthermore, a limit concentration of 5 g L-1 is recommended for fertigation because there was some change in uniformity when this value was exceeded. Finally, it is important to emphasize the need for further studies to reduce water application and nutrients and increase distribution uniformity in precision irrigation. However, the techniques of statistical control regarding the process quality, applied in this study, can be available to identify and diagnose process variability. Lastly, this study has shown that photovoltaic solar energy can be applied in irrigation, but charge controllers and battery banks should not be applied in photovoltaic fertigation systems.